MORFOLOGI KELENJAR LUDAH KAMBING, KUCING DAN BABI: DENGAN TINJAUAN KHUSUS PADA DISTRIBUSI DAN KANDUNGAN KARBOHIDRAT (The Morphology of Salivary Glands of Goat, Cat, and Pig: With Special Reference to The Distribution and Carbohydrate Content) - Adnyane, I Ketut Mudite (Jurnal Kedokteran Hewan, 2009)
This research aimed to compare the morphology and carbohydrate content of parotid andmandibular glands of goat, cat and pig (herbivore, carnivore and omnivore). The microscopic observationwas done using histochemical method with hematoksilin eosin (HE), alcian blue (AB) pH 2.5 andperiodic acid Schiff (PAS) staining methods.The results showed that the parotid and mandibular glandsconsist of acinar cells and ducts. The parotid gland of goat and pig were serous while mixed in the cat.The mandibular gland of goat, cat and pig were mixed type. The acinar of mandibular gland is composedof serous and mucous cells in which the mucous cell predominates. The AB and PAS stain showed weakto high concentration of acid and neutral carbohydrates found in the mucous cells of mandibular gland.However, these carbohydrates were not found in the serous cells of both glands, while acid carbohydratewas found in the parotid gland of cat. The present result suggested that the carbohydrates in the salivaof the goat, cat and pig might be produced mainly by the mucous cells.Keywords: parotid gland, mandibular gland, PAS, AB pH 2.5